2014
DOI: 10.1089/jmf.2013.0154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron and Fat in a Diet Containing Green Tea Extract (Camellia sinensis) on the Antioxidant Capacity of Some Organs and the mRNA Expression of Specific Genes in Mice

Abstract: The hypothesis that iron and fat in the diet may affect green tea extract (GTE) bioactivity, in particular antioxidant capacity and gene expression, was proposed and tested in mice. Thirty mice were randomly assigned to have for 37 days free access to standard or high-fat diets with or without GTE and ferrous lactate. Mice were euthanized and specific organs were removed. Total antioxidant capacity (TAC) was measured using the ferric reducing antioxidant power (FRAP) and oxygen radical absorbance capacity assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…A current study has supported that the combined chelation treatment synergized mobilization of labile iron pools in Huh7 cells, in which the DFX + DFP treatment was the most effective [45]. Though effect of green tea consumption on iron absorption is not conclusive definitely, we believe that it will not affect our study [46,47].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…A current study has supported that the combined chelation treatment synergized mobilization of labile iron pools in Huh7 cells, in which the DFX + DFP treatment was the most effective [45]. Though effect of green tea consumption on iron absorption is not conclusive definitely, we believe that it will not affect our study [46,47].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…The difference in AC between brain and the other organs was highly significant ( p < 0.001) and was probably a result of the blood-brain barrier limiting PP accumulation. In another study, the brain also had the lowest AC among the organs in a rats given a green tea extract high in catechins and other PP [15]. Another analysis showed that FRAP AC of brain tissue was lowest compared to the other organs tested [16].…”
Section: Resultsmentioning
confidence: 99%
“…Dietary polyphenols have been studied for their potential beneficial effect on human health and disease prevention [2,3,[8][9][10][11][12][13][14][44][45][46][47]. Nevertheless, their bioactivity is dependent on their bioavailability, which differs in the various polyphenol subcategories [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary models rich in fruits, vegetables, cereals, legumes, nuts, and a plethora of natural functional foods and beverages, are linked with high intake of polyphenols [4][5][6][7][8][9]. Their structure, with hydroxyl groups, promotes their possible antioxidant activity in human organisms, while antibacterial, anti-inflammatory, cardioprotective, antidiabetic, and anticancer activities have also been studied due to either antioxidative properties or possible effects on gene expression, by modulating protein synthesis and specific metabolic pathways related to diseases' pathophysiology [2,3,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%